KREDIT TANPA BUNGA (AL-QARD AL-HASAN) TEORI DAN REALITA - Hidayatina, Hidayatina (Faculty of Islamic Economics and Business, IAIN Lhokseumawe, 2020)
Interest-free credit (al-Qardh al-Hasan) is a non-ribawi social fund for Muslims who need help, both productive and consumptive. However, the funds sourced from the philanthropy of muslim benefactors became less maximal due to the lack of awareness from the recipients of al-qard al-hasan funds as well as the absence of supervision and coaching by the fund's management agency. And the financing of al-qard al-hasan which is also a form of Islamic protection against the weak is able to help the government overcome their problems. Keywords: al-Qarh al-Hasan, zakat management institutions, Sharia financial institutions Abstrak Kredit tanpa bunga (al-Qardh al-Hasan) merupakan dana sosial non ribawi bagi umat Islam yang membutuhkan bantuan, baik produktif maupun konsumtif. Namun, dana yang bersumber dari filantropi dermawan muslim menjadi kurang maksimal karena kurangnya kesadaran dari penerima dana al-qard al-hasan serta tidak adanya pengawasan dan pembinaan oleh pengelola dana tersebut. Dan pembiayaan al-qard al-hasan yang juga merupakan salah satu bentuk perlindungan Islam terhadap kaum lemah mampu membantu pemerintah mengatasi permasalahan mereka. Kata kunci: al-Qarh al-Hasan, lembaga pengelola zakat, lembaga keuangan syariah